Survivorship care plan experiences among childhood acute lymphoblastic leukemia patients and their families - Samantha T. Pannier (BMC Pediatrics, 2019)
Abstract Background As survivorship care plan (SCP) use among childhood cancer survivors and their families has not been extensively researched, we report on their experiences with receiving an SCP after the completion of therapy. Methods Eligible patients had acute lymphoblastic leukemia, completed therapy, and had no evidence of disease at enrollment. Patients aged 7 or older (N = 13) and at least one parent (N = 23 for 20 total patients) were surveyed and completed assessments at enrollment (Time 1, T1), SCP delivery (Time 2, T2), and follow-up (Time 3, T3) (retention 90.9%). Surveys assessed the delivery process and SCP format. McNemar tests were used to assess change from T2-T3. Results Satisfaction with the SCP was generally high among parents. At T1 the majority of parents (69.6%) thought the SCP should be delivered after treatment but by T3 most preferred the plan to be delivered before the end of treatment (60.9%). While 95.7% of parents intended to share their child’s SCP with another provider, family, or school at T2, only 60.9% had done so by T3 (P < 0.01). At both T2 and T3, 100% of parents agreed that the SCP would help make decisions about their child’s future health care. Most patients at T3 (83.3%) felt they had learned something new from their SCP. Conclusions Pediatric oncology patients and families feel SCPs are useful and will help them make decisions about health care in the future.